2003
DOI: 10.1016/s0029-7844(03)00858-5
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Vaginosis in Sexually Experienced and Non–Sexually Experienced Young Women Entering the Military

Abstract: Among these diverse young women, bacterial vaginosis occurs commonly in both sexually experienced and inexperienced young women and differs by race and ethnicity. The pH colorimetric test and Papanicolaou smear performed moderately well as screening tools for bacterial vaginosis. The inverse relationship of bacterial vaginosis with hormonal contraceptive use and its direct relationship with C. trachomatis need further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(43 citation statements)
references
References 32 publications
1
38
2
2
Order By: Relevance
“…Factors that were associated with multiple BV episodes in this analysis (trichomoniasis 36 , lack of contraceptive use [37][38][39][40][41] , and PID 9 ) have also been reported to be factors in other analyses that evaluated risks associated with single episodes of BV. In addition, our analysis suggests that girls with more frequent disruptions of vaginal flora (2+ BV group) may be more likely than the 1 BV group to be diagnosed with PID.…”
Section: Discussionmentioning
confidence: 51%
“…Factors that were associated with multiple BV episodes in this analysis (trichomoniasis 36 , lack of contraceptive use [37][38][39][40][41] , and PID 9 ) have also been reported to be factors in other analyses that evaluated risks associated with single episodes of BV. In addition, our analysis suggests that girls with more frequent disruptions of vaginal flora (2+ BV group) may be more likely than the 1 BV group to be diagnosed with PID.…”
Section: Discussionmentioning
confidence: 51%
“…Epidemiologic studies are strongly supportive of sexual transmission of BV pathogens and most experts believe that BV does not occur in women who have never had vaginal intercourse (Yen et al, 2003). However, BV can develop in women who have never had sexual intercourse, probably because of other factors that may destabilize the normal vaginal flora such as douching and wearing of tight fitting underwear (Papanikolaou et al, 2002;Fethers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the incidence of symptomatic women are bacterial vaginosis (40-45%), vaginal candidiasis (20-25%), and trichomoniasis (15-20%); yet 7-72% of women with vaginitis may remain undiagnosed [2] . The commonest causes of altered vaginal discharge in women of reproductive age, infective (non-sexually transmitted) bacterial vaginosis Candida and infective (sexually transmitted) trichomonas vaginalis or non-infective foreign bodies (e.g.retained tampons, condoms,) [5] . The causes of vaginal discharge may be physiological or pathological conditions including cervicitis, aerobic vaginitis, atrophic vaginitis and mucoid ectopy.…”
Section: Introductionmentioning
confidence: 99%